plz answer this........
Attachments:
![](https://hi-static.z-dn.net/files/d36/cc43f3379c7166b05c6d4f1f090c0517.jpg)
Answers
Answered by
1
Using (a-b)² identity ,
(a-b)² = a² -2ab + b²
(3√5 - 4√3 ) ² = (3√5)² - 2×3√5×4√3 + (4√3)²
=> 45 - 24√15 + 36
=> 81 - 24√15
= 3 ( 27 + 8√15 )
Please Mark As Brainliest
Answered by
1
Answer:
I hope its helpfull for you.
Attachments:
![](https://hi-static.z-dn.net/files/d10/dd11d8dac1cab0c29280a46bf649393a.jpg)
Similar questions
English,
6 months ago
English,
6 months ago
Math,
6 months ago
Science,
1 year ago
Computer Science,
1 year ago